Impact of intellectual capital on organizational performance through intrinsic motivation in higher education institutions - Patricia Alexandra Uriguen Aguirre; Beatrice Elcira Avolio Alecchi (Cogent Business & Management, 2023)
The purpose of this research is to analyze the relationship between intellectual capital and organizational performance with the mediating rol of intrinsic motivation in higher education institutions. We conducted an empirical study with a sample of 815 employees from public and private universities in Ecuador. Data were obtained from an instrument adapted the previous researchadministered to faculty and administrative staff in management positions. A structural equation modelling approach was used to analyze the relationships between variables and their magnitude and direction. The results showed a significant relationship between intellectual capital and organizational performance, with a partial mediation of intrinsic motivation. No significant differences were found in the effect of intellectual capital between public and private universities. Managers who aim to improve the performance of their organizations with their intellectual capital can benefit from the intrinsic motivation of their employees. This research shows intrinsic motivation as a mediator between intellectual capital and organizational performance, but also analyzes their relationships based on the Self-Determination Theory, which is a novelty according to the existing literature.
Keywords: M10; M54; I23; 650; Intellectual capital; organizational performance; intrinsic motivation; higher education institutions; self-determination theory